PEMANFAATAN PUSAT SUMBER BELAJAR DALAM MENINGKATKAN HASIL BELAJAR - Imam Subqi (UNDIKMA, 2016)
Learning Resource Centre has an important role in fostering quality learning outcomes. The learning process that occurs in the institutions of education and training is no longer possible to do with a lot of